Religious understanding of relationship between science and religion as a dialogue of worldwides - Zakovych, Mykolay Mykhailovych (Ukrai͏̈ns'ke relihijeznavstvo, 2017)
The question of the attitude and perception of some denomination of the achievements of scientific knowledge has a long history. Theologians have always sought to eliminate science from the sphere of spiritual life. However, nowadays, as this article testifies, the theologians aspire to put science for ourselves in a different way, to prove the possibility of a dialogic coexistence of science and religion.